Pelatihan Pembuatan Pupuk Organik Cair Air Beras Bagi Ibu-Ibu Anggota PW Rayon 4 GKI Getsemani Kotaraja Jayapura - Henderina J. Keiluhu; Elieser Elieser; Euniche R.P.F. Ramandey; Evie l. Warikar; Lisye I. Zebua; Daniel Z.K. Wambrauw; Yulindra M. Numberi; Nurlita Dianingsih (Bakti Hayati: Jurnal Pengabdian Indonesia, 2023)
Kitchen waste is the result of household activities which include organic and inorganic waste in the form of liquid and solid waste.  Basically, kitchen organic waste can still be used to produce of Liquid Organic Fertilizer (POC). The material presented in the socialization of this community service activity aims to (1) introduce useful plant species for household needs that can be grown in pots, and (2) provide knowledge on making and using Liquid Organic Fertilizer (POC) from rice water. Participants of this activity is the members of the Women’s Fellowasip (PW) GKI Getsemani Kotaraja Jayapura.  This training Activity was carried out from 26th of August to 3rd of September 2021, during the COVID 19 pandemic, so the socialization of the material was carried out in the form of online presentations, while practical material was provided via print out material.  Then, the participants practiced making rice water POC and the planted useful plants in pots independently at their respective homes.  Each participant was given a package consisting of compost soil, EM4, flower pots, also flower and plant seeds.  The results of the implementation of this activity showed an increase in the understanding and knowledge of the training participants about useful plant species for household needs and making process of POC, and then being able to use it to fertilize useful plants around the house. Keyword: rice water waste; Liquid Organic Fertilizer; POC; pot gardening; GKI Getsemani Kotaraja; Jayapura.